JENG MANIZKU : Sinergitas KWT Arimbi dan CSR Pertamina DPPU Adisucipto Untuk Ketahanan Pangan Masyarakat Sambilegi Kidul di Masa Pandemi Covid-19 - Beti Nur Hayati; Erlangga Fajar Satrio; Irfan Hibatulaziz (UIN Siber Syekh Nurjati Cirebon, 2022)
This study looks at the synergy between Pertamina DPPU Adisucipto Yogyakarta and KWT Arimbi in an effort to survive the Sambilegi Kidul community during the Covid-19 pandemic in the JENG MANIZKU CSR program (A span of my Family Nutrition page). The research method used is descriptive qualitative method with data collection techniques using interviews, observations and documentation studies. This research was conducted from February to Maret 2022. The results of this study indicate that the form of synergy between the company and the community is realized by Pertamina DPPU Adisucipto Yogyakarta providing assistance for vegetable, fruit, fish seeds, and equipment for cultivation activities. In addition, Pertamina DPPU Adisucipto also provides assistance in planting. Meanwhile, KWT Arimbi acts as a partner who promotes agriculture to the community so that they can participate in planting activities to meet food availability during the Covid-19 pandemic.